Popliteal aneurysm: Complication acute distal embolism - Bergalli, Luis; Carriquiry, Luis; Olivera, Daniel E. (Cirugía del Uruguay, 1979)
A patient suffering from Teft popliteal aneurysm complicated by severe ischemia due to distal embolism was subject to vascular exclusion and by - pass with saphenous vein. Short - term clinical and arteriographic evolution was good. Finally, clinical and therapeutic concepts are analyzed, the authors insist that aggressive surgical conduct of asymptomatic aneurysm is essential, restoring distal circulation in cases comp!icated by thrombosis or embolism.